(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Solid assumes a significant part in the infrastructural advancement and economy of a country. Considering these components the materials utilized in the readiness of cement have gotten the most sought after assets in this world. Bethamcherla is a town situated in the Kurnool region of Andhra Pradesh, which is notable for the ground surface marble stone, utilized in deck pieces and abodes. The waste produced from the Bethamcherla marble enterprises causes natural issues. Consequently the reuse of this waste material can be highlighted to convey negligible expense concrete byout setting with Bethamcherla marble stone waste and to diminish removal and contamination issues from usage of stone waste.